Effect of empowerment, training, compensation, and appraisal on UTAR lecturer‘s retention. - Ng, Eric Chee Hong; Lam, Zheng Hao; Lee, Chak Tak; Ng, Yee Kiat; Ong, Yong Guan (2011)
The main objective of this research project is to analyze the factors that affecting retention of lecturers in education industry. The factors that will affect the retention which will be discussed later included empowerment, training, compensation, and appraisal. Past study done by others researchers will help to develop the hypothesis in this research project. Researchers had conducted the survey in UTAR Perak Campus to test the relationship between those factors and lecturer‘s retention. A sample size of 280 respondents in a questionnaire method had been conducted. Researchers used the SPSS program to run the reliability analysis, significance analysis, and correlation coefficient analysis to analyze and interpret the data. As a result, researchers found that empowerment, training, compensation, and appraisal have significant positive relationship with lecturer‘s retention. Next, researchers discussed the findings and suggested some recommendation for all the factors. Lastly, researchers come out the future study and conclusion to close up the entire study.